Exploring the clinical significance of IL-38 correlation with PD-1, CTLA-4, and FOXP3 in colorectal cancer draining lymph nodes - Yuan, Liuhong; Tan, Zhenyu; Huang, Junjie; Chen, Feier; Hambly, Brett D.; Bao, Shisan; Tao, Kun (Frontiers in Immunology, 2024)
Colorectal cancer (CRC) presents a substantial challenge characterized by unacceptably high mortality and morbidity, primarily attributed to delayed diagnosis and reliance on palliative care. The immune response of the host plays a pivotal role in carcinogenesis, with IL-38 emerging as a potential protective factor in CRC. However, the precise involvement of IL-38 among various leucocytes, its interactions with PD-1/PD-L1, and its impact on metastasis require further elucidation. Our investigation revealed a significant correlation between IL-38 expression and metastasis, particularly concerning survival and interactions among diverse leucocytes within draining lymph nodes. In the mesentery lymph nodes, we observed an inverse correlation between IL-38 expression and stages of lymph node invasions (TNM), invasion depth, distance, and differentiation. This aligns with an overall survival advantage associated with higher IL-38 expression in CRC patients' nodes compared to lower levels, as well as elevated IL-38 expression on CD4 + or CD8 + cells. Notably, a distinct subset of patients characterized by IL-38 high /PD-1 low expression exhibited superior survival outcomes compared to other combinations. Our findings demonstrate that IL-38 expression in colorectal regional nodes from CRC patients is inversely correlated with PD-1/PD-L1 but positively correlated with infiltrating CD4 + or CD8 + lymphocytes. The combined assessment of IL-38 and PD-1 expression in colorectal regional nodes emerges as a promising biomarker for predicting the prognosis of CRC.